Analisis Kesulitan Peserta Didik Dalam Pemecahan Masalah Matematika Pada Materi Operasi Hitung Pecahan Di Tingkat Sekolah Dasar - Aryo Sagara, Muhammad; Fitriani, Fitriani; Nurhidayat, Nurhidayat; Kasma, Kasma; Salman, Risnawati; Musdalifah, Musdalifah (Lembaga Bale Literasi, 2023)
Students have difficulty exploring mathematics learning. There have been errors in learning operations to calculate fractions, mistakes in working on fraction problems. One of the skills that students need to have is the ability to solve problems, but in the learning process they often have difficulty in this regard. This research tries to investigate the variables that influence students' challenges in solving mathematical problems and examines the mistakes students make in solving these problems. Errors that occur to students in fraction calculation operations occur during the process of understanding the questions and when checking the results of their work again. Researchers have applied a qualitative research approach. In this research, the researcher is directly involved in the conditions and settings of the phenomenon being studied to obtain the reality of understanding and inductive thinking processes. Therefore, researchers are expected to always focus their attention on the context being researched or on the context of reality. In the research methodology, students tend to experience difficulties when working on questions. Because students do not yet understand the concepts of multiplication fractions and ordinary fractions, in the learning process the teacher teaches students about fraction material in stages to help students understand the concept of fractions.